Role of oxidative stress in reproductive toxicity induced by co-administration of chloramphenicol and multivitamin–haematinics complex in rats (2010)
Concurrent administration of chloramphenicol (CAP) with multivitamin–haematinics complex (MHC) is a common practice to cushioning anticipated anaemic effect of CAP in most developing countries. This study investigated the mechanism involved in CAP-induced reproductive toxicity as well as the effects of its co-administration with MHC in male rats. CAP and MHC were administered orally at therapeutic doses of 28 mg ⁄ kg body-weight and 0.08 ml ⁄ kg body-weight, respectively, every 6 hr for 10 days. After exposure, while there was body-weight loss in CAP, MHC and CAP plus MHC-treated animals, there were no treatment-related changes in the absolute and relative weights of the testes in all treated groups. Alone, MHC treatment markedly decreased catalase (CAT), glutathione S-transferase (GST), and 5¢ nucleotidase (5¢ NTD) activities whereas it resulted in significant increase in superoxide dismutase (SOD) activity. Activities of SOD, CAT and GST as well as H2O2 levels were not significantly affected in CAP and CAP plus MHC-treated rats whereas GSH level and 5¢ NTD activity were markedly decreased in CAP plus MHC-treated rats. Significant increase in testicular alkaline phosphatase activity, lipid peroxidation and sperm abnormalities were accompanied by reduction in epididymal sperm number, sperm motility and live–dead ratio in all treatment groups whereas aminotransferase activities were unaffected. Treatment-related degeneration of the testes was evident in all treated animals. In summary, while MHC-induced testicular toxicity via oxidative stress, CAP did not and their combination is implicated in reproductive dysfunction within the time course of our investigation.